Long noncoding RNA as an emerging regulator of endoderm differentiation: progress and perspectives - Jie Yang; Donghui Zhang; Wei Jiang (Cell Regeneration)
Abstract Accumulated studies have demonstrated that long noncoding RNAs (lncRNAs) play crucial regulatory roles in diverse biological processes, such as embryonic development and cell differentiation. Comprehensive transcriptome analysis identifies extensive lncRNAs, gradually elucidating their functions across various contexts. Recent studies have highlighted the essential role of lncRNAs in definitive endoderm differentiation, underscoring their importance in early development. In this review, we have analyzed the features of overlapping, proximal, and desert lncRNAs, classified by genomic location, in pluripotent stem cells (PSCs) and the differentiation derivatives. Furthermore, we focus on the endoderm lineage and review the latest advancements in lncRNA identification and their distinct regulatory mechanisms. By consolidating current knowledge, we aim to provide a clearer perspective on how lncRNAs contribute to endoderm differentiation in different manners.